The role of home medication storage location in increasing medication adherence for middle-aged and older adults - Gualtieri, Lisa; Shaveet, Eden; Estime, Brandon; Patel, Avi (Frontiers in Digital Health, 2022)
Background: Over 50% of US adults do not take their prescriptions as prescribed, which is responsible for 33% to 69% of hospital admissions and 125,000 deaths annually. Given the higher prevalence of prescription drug use among middle-aged and older adult populations, promoting medication adherence is of particular importance with these age groups. Two speculated facilitators of medication adherence are home medication storage location and the use of digital health devices. Objective: Our objective was to use survey data to investigate the associations between medication storage location and medication adherence among adults 40 years and older. Additionally, we aimed to report preliminary findings about the associations between use of digital health devices and medication adherence in this same population. Methods: We conducted primary analysis of data sampled from a home medication management survey deployed in November 2021 (n=580). We conducted exploratory analyses by way of chi2 tests and creation of bivariate logistic regression models. Results: The most commonly used storage locations by our sample were nightstand drawers (27%), kitchen cabinets (25%), and atop bedroom nightstands (23%). Several medication storage locations were significantly associated with decreased odds of having ever forgotten to intake a medication, including kitchen drawers, in refrigerators, atop bedroom nightstands, in nightstand drawers, and backpacks, purses, or bags. Two home medication storage locations were significantly associated with increased odds of having ever forgotten to intake a medication: kitchen cabinets and bathroom vanities. Further, most (94%) survey respondents indicated they would be receptive to guidance about where to store their medications. Conclusions: Given that patients often need to select a location to store their medication in their homes and that some storage locations are associated with adherence; we believe that an intervention to optimize storage selection may support increased adherence. The impact of digital health device usage paired with optimized home medication storage location on medication adherence in middle-aged and older adult populations remains unknown but is worthy of further investigation. Further, we plan to investigate how new device designs can consider specific medication storage locations and contextual cues related to location to promote adherence more effectively.